(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2024)
This study aimed to determine if the attitude toward mathematics of BSE and BEED students in DMMMSU NLUC is significantly correlated to their Mathematics performance. Specifically, it seeks answers to the following questions: What is the profile of the students enrolled in Mathematics along sex, CAT Result in Mathematics and IQ level. What is the attitude of students towards Mathematics? What is performance of the respondents in Mathematics? Is there a significant relationship between profile variables and attitude towards Mathematics profile variables and performance in Mathematics, attitude toward Mathematics and Mathematics performance? Which among the variables are predictors of Mathematics performance? What action plan can be proposed to enhance the level of performance and attitude of the students in Mathematics? This study utilized the descriptive method of investigation. This is best fitted to the study because this method involves describing, recording, analyzing and interpreting conditions that exist. It also includes some forms of comparison and contrast and discovers relationship between existing non-manipulative variables. The respondents are two classes enrolled in Basic Mathematics and Contemporary Mathematics for the SY 2014-2015. Their attitude towards Mathematics were obtained using an attitude inventory, their IQ and CAT Math results were obtained from the Guidance Office and their performance were taken from their final grade in Mathematics. The attitude of students toward Mathematics and their performance in Mathematics were described, analyzed, compared, and interpreted. Mean was used to describe the attitude and performance in Mathematics. Furthermore, the relationship of the aforementioned variables will be obtained. Hence, the use of statistics of correlation under descriptive method was also used. The following are the salient findings of this study: Majority of the Mathematics students are females with fair to good performance in the Math CAT and IQ level. The students have positive to highly positive attitude towards Mathematics. The students have very good performance in Mathematics.IQ and CAT performance are significantly correlated with Mathematics performance. CAT significantly correlates with attitude and attitude is significantly correlated with Mathematics performance. In the light of the above-stated findings, the following conclusions are drawn: The Math classes are dominated with females who have only fairly satisfactory to satisfactory IQ levels and performance in the CAT along Mathematics. A greater majority of the students find mathematics enjoyable, interesting and fun. Most of the students have acquired the needed competencies in Mathematics. They are good in computation, comprehension and problem solving. Those who have high IQ and high CAT results perform excellently in Mathematics. The better is the attitude towards Mathematics the higher is the performance in the subject. Attitude has a positive impact of performance in Mathematics. Based on the conclusions, the researcher offered the following recommendations: Teachers are encouraged to customize their instruction and improve the use of modernized and innovative teaching techniques and strategies to enhance performance and attitude of students toward Mathematics. The Mathematics teachers especially the Math Club Adviser should consider the implementation of the Action Plan to improve attitude and performance in Mathematics. The administrators should support the implementation of the Action Plan by providing the opportunities and logistics for its accomplishment. The Action Plan should be considered for adoption by other HEIs in La Union with the administrators and Head of Mathematics Department planning its mechanics of implementation. A research on the effectiveness of the proposed action plan when implemented be conducted as basis for revisions and improvement.